Forecasting the Number of BMT NU Lenteng Branch Customers Using the Single Exponential Smoothing Method - Munawwarah, Siti; Sarifah, Luluk (Zeta - Math Journal, 2025)
The presence of financial institutions greatly helps the country in terms of economy, including Islamic financial institutions such as BMT NU Lenteng Branch which was established in 2014. For BMT NU, the existence of customers greatly influences the continuity of the work process. Therefore, in order to facilitate the preparation of the next work plan, a customer forecasting technique is needed to determine the number of saving customers in the next period, which can fluctuate every year. For this study, data on the number of savers was used from 2014-2023, then for forecasting using the Single Exponential Smoothing method, a method that focuses on finding stability values. The advantage of this method lies in its ease of operation which is relatively simple. To determine the level of accuracy obtained from the forecasting results, the Mean Absolute Deviation (MAD), Mean Squared Error (MSE), and Mean Absolute Percentage Error (MAPE) methods are used. From the results of the research that has been carried out, it was found that the best alpha value for forecasting is at alpha 0,9 with a forecasting result of 10.065,3. The error calculation obtained for the last 10 years of data is MAD = 1.050,037676, MSE = 1.622.018,167, and MAPE = 25%. While for the last 5 years of data, MAD = 1.415,6342, MSE = 2.528.041,621, and MAPE = 19%.